Tip-2 Bulanık Öbekleme Yöntemleri İle Zaman Serilerinin Modellenmesi - Dodurka, Mehmet Furkan (Fen Bilimleri Enstitüsü, 2014)
Zaman serileri ile süreç modelleri elde edip, süreç modelleri ile ileriye yönelik kestirimlerde bulunma ekonomi, mühendislik, jeoloji, meteoroloji gibi birçok alanda etkin bir şekilde kullanılmaktadır. Model eldesi için klasik yaklaşımda, doğrusal istatiksel modeller kullanılmaktadır. Ancak model elde etmek için kullanılan verilerde yer alan belirsizlikler ve modellenen süreçlerde yer alan doğrusal olmayan özellikler nedeniyle doğrusal modeller her zaman süreçleri doğru bir şekilde modelleyememektedirler. Yukarıda bahsedilen belirsizliği fazla ve doğrusal olmayan süreçlerin modellenmesi için en etkili yöntemlerden biri bulanık kümeleri içeren sistemlerle ile oluşturulan modellerdir. Ancak son yıllarda literatürde yapılan çalışmalar göstermiştir ki Tip-1 bulanık kümeler belirsizliklerin üstesinde gelmede yeterince başarılı olamamaktadırlar bu yüzden literatürde Tip-2 bulanık kümelerle ilgili birçok başarılı çalışma sunulmuştur. Çünkü Tip-2 bulanık sistemler sahip olduğu belirsizlik izdüşümü sayesinde belirsizliğin üstesinden gelmede Tip-1 bulanık sistemlere göre daha başarılıdır. Bu çalışmada da Tip-2 kümelerin özel bir hali olan Aralık Değerli Tip-2 bulanık sistemleri ile zaman serilerinin modellenmesi üzerinde çalışılmıştır.  Bu çalışmada zaman serilerinin modellenmesinde kullanılacak Tip-2 bulanık modellerin eldesi için gözetimli öğrenme ve gözetimsiz öğrenme yöntemlerinden yararlanılmıştır. Bu amaçla Tip-1 bulanık öbekleme yöntemleri ile modelleme yaklaşımı, ADT2 bulanık sistemlerine genişletilmiştir. Bilindiği gibi öbekleme yöntemleri gözetimsiz öğrenme yöntemleri oldukları için veri hakkında çok az bilgi sahibi olunsa bile veriden bilgi edimini sağlarlar. Bu çalışmada bulanık sistemin öncül kısımları belirlemek için kullanılan Tip-1 bulanık kümelerle öbekleme yöntemi yerine ADT2 bulanık kümelerle öbekleme yöntemi kullanılmıştır. Literatürde ADT2 bulanık kümeler için önerilmiş ADT2 bulanık c-ortalama öbekleme algoritması genişletilerek Tip-1 bulanık kümeler için önerilen Gustafson-Kessel algoritması için ADT2 bulanık kümelerle öbekleme yöntemi geliştirilmiştir. ADT2 bulanık modelin sonuç parametrelerinin belirlenmesinde ise gözetimli öğrenme yöntemlerine başvurulmuştur. Fakat ADT2 bulanık modelin içerisinde yer alan tip indirgeme mekanizmasının iteratif doğası yüzünden, gözetimli öğrenme probleminin çözümünde en küçük kareler gibi iteratif olmayan optimizasyon yöntemleri doğrusal olmayan ve iteratif optimizasyon yöntemlerine başvurulmuştur.  Önerilen modelleme yönteminin başarımını ölçmek için farklı karakteristiklere sahip zaman serileri modelleme ve tahminleme çalışılması yapılmış ve modellerin başarımları doğrusal ARMA modelleri ve literatürde sıklıkla kullanılan ANFIS yöntemi karşılaştırılmıştır. Karşılaştırmalar sonucunda ADT2 bulanık modellerin başarımının birinci zaman serisi için her iki yönteme göre oldukça iyi sonuç verdiği, ikinci örnek içinse ADT2 bulanık modelin başarımının ilk örneğe kıyasla az olduğu ancak başarım azda olsa diğer iki yönteme göre daha iyi sonuç verdiği gözlemlenmiştir. Bu sonuçlar ışığında ADT2 bulanık modellerin süreçlerdeki belirsizliği ve doğrusal olmayan karakteristiği ifade etmede başarılı olduğu sonucu varılmıştır. Ancak ADT2 bulanık sistemlerle modelleme yapılmak istendiğinde diğer modellere göre modellenme öncesinde belirlenmesi gereken parametre sayısı ve işlem yükü artmaktadır. Bu durumda ADT2 bulanık sistemlerle modelleme yapılıp yapılmamasına, modellenmek istenen sürecin sahip olduğu doğrusal olmayan nitelik ve belirsizlik gibi özelliklere bakılarak karar verilmelidir.

Time series are observations that each observation is recorded at specific time, which can be recorded discrete and continuous. In many applications such as economics, engineering, geology, time series are used modelling the processes for predicting future values of them. In the classical approach for modelling of processes linear and statistical models are mostly used. However due to fact that having uncertainness and nonlinearities in the processes being aimed to model, mostly these linear and statistical models can not represent processes in an accurately way To model the nonlinear and uncertain process mentioned above, one of the efficient method is using fuzzy sets and systems for modelling. Because the fuzzy sets are extension of the classical set approach moreover in the classical set approach each entity must belong to a set or vice versa must not belong, but in the fuzzy logic approach the belonging of an entity to a set can be represented partially. So that vagueness can be represented in an efficiently way. Nevertheless, recent studies shows that Type-1 fuzzy sets cannot handle the uncertainties sufficiently. So for that reason many successful studies that using Type-2 sets and systems are presented in the literature recently. In Type-2 fuzzy sets membership of an entity also represented with fuzzy sets where as in Type-1 fuzzy sets membership represented with crisps numbers. On the other hand, working with Type-2 fuzzy systems  leads to more  computational  complexity  according  to  the  study  with  Type-1  fuzzy  counterparts. So a special expressions of Type-2 fuzzy sets called Interval Type-2 (IT2) fuzzy sets was proposed.  In this study, in the modeling of time series Interval Type-2 fuzzy sets are used.  Clustering methods are unsupervised methods that provide the obtaining knowledge from data with a too few information about data. For example for a data set given in matrix about patients  the rows are features of patients such as symptoms, diagnostics, age, sex and each column represents a different patient. The aim is here to specify the similar patients in other words grouping the patients so the clustering procedure is dividing a set into subsets having similar entities. Here the similarity term arisen from the metric distance. The clusters have two components the first one is prototype that represents centers of clusters which can be single point or functions and second one is partition matrix which includes the membership of set entities to each cluster. In literature Fuzzy C-Means (FCM) clustering method are presented by Bezdek enabling to derive the fuzzy subsets from a set i.e. fuzzy clusters. However, in FCM approach all obtained clusters have same shapes and orientation. Therefore, Gustaffson and Kessel presented a new algorithm providing to obtain each cluster in different shapes and orientation. Recently Hwang and Rhee extended FCM algorithm to IT2 Fuzzy sets to obtain clusters as IT2 Fuzzy sets. In this study, IT2-FCM approach extended to derive IT2 fuzzy clusters as in Gustaffson Kessel clustering approach. Time series models can be classified according to their forms for both linear and nonlinear models such as Auto Regressive (AR), Moving Average (MA) and Auto Regressive and Moving Average (ARMA) models. In AR models, process output just depends of the previous observation of processes, in MA models output just depends the previous noises i.e. prediction errors and for ARMA models the output depend both previous observation of processes and noises. In this study only auto regressive models are considered  In this thesis, an approach for modelling time series with IT2 fuzzy models are presented. In the proposed approach both unsupervised and supervised methods are used in modelling. For this, the method of modelling Type-1 fuzzy system with Type-1 fuzzy clustering approach are extended for IT2 fuzzy models. In this study IT2, fuzzy clustering approach is used for obtaining antecedent parts of fuzzy systems. For antecedent's parts, each fuzzy set used in represented with gauss membership functions. Gauss membership function parameters are extracted from by using IT2 fuzzy partition matrix. For obtaining consequents parts of the IT2 fuzzy model the supervised learning methods are used. In IT2 fuzzy system consequents, parts consist of from linear polynomial functions. So supervised learning approach is used for obtaining parameters of polynomial functions. In the supervised method the objective is the minimize the error between model output and observed output. Therefore, that it becomes an optimization problem. Here mean root square error criterion is used for criterion to be minimized.   However, because of having iterative nature of type reducer used in IT2 fuzzy models, the non-iterative optimization methods such as the least squares cannot be used for solving learning problem instead the iterative and nonlinear optimization methods are used for optimization. For getting lower, upper bounds, and initial point, for optimization method a heuristic approach based on least squares method is used.  To observe the performance of proposed modelling with IT2 fuzzy clustering method performance indices are used such as mean root square error, percentage of mean absolute deviation and variance accounted for. The proposed method compared with two well-known methods linear ARMA model family and ANFIS approach, which used for learning of Type-1 fuzzy models.  For the comparison studies, two example time series having different characteristics are used. The first one is a benchmark time series the sunspots, especially used in nonlinear time series modeling methods with no clear seasonality and trend effects. The other time series are monthly change of soil temperature, which has strong seasonality and trend effects. For the modelling study, time series are divided into three parts. The first one is used for training, second one is used for validation and last one is used for testing. For observing generalization capabilities and performances of modelling approaches performance indices are calculated for the testing part for each methods.  By looking results of comparisons for the sun spots time series, the fuzzy approaches ADT2 based and ANFIS  outperformed ARMO model family distinctly but also ADT2 have more better performance over ANFIS approach especially for the testing phase, for the change of monthly soil temperature time series ADT2 based model also has better performance than other two methods but not as intense performance as sun spot time series' performance, because the trend and seasonal components have strong influence than residual part of time series..  Therefore, in consequence of results it can be said that ADT2 fuzzy cluster based modelling approach has capability of handling uncertainty and represent nonlinearity. However, many parameters must be determined for modelling with ADT2 fuzzy cluster based approach furthermore the computational cost of ADT2 based modeling is rather high. Therefore, someone who wants to use ADT2 fuzzy clustering approach for modelling of a process must determine process's uncertainties and nonlinearities to decide the trade of between handling uncertainties, nonlinearities and parameter counts, computation costs.
Time Series Modelling With Type-2 Fuzzy Clustering Methods
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: Tip-2 Bulanık Zaman Serileri; Bulanık Öbekleme; Tip-2 Bulanık Model; Tip-2 Bulanık Sistem; Bulanık Modelleme; Doğrusal Olmayan Zaman Serilerin Modellenmesi; Type-2 Fuzzy Time Series; Fuzzy Clustering; Type-2 Fuzzy Model; Type-2 Fuzzy System; Fuzzy Modelling; Nonlinear Time Series Modelling